Supplementing urban water supply with rainwater harvesting in Accra, Ghana - Owusu, K.; Kofi Teye, J. (International Journal of Water Resources Development, 2014)
This article examines the challenges associated with rainwater harvesting and usage in peri-urban Accra. Data collected from 357 heads of household reveal that rainwater harvesting has the potential to supplement existing water sources in peri-urban Accra. However, high investment costs for rainwater harvesting facilities, short-term tenancy arrangements, the perception that rainwater is not clean, and the unique dry climate of the Accra Plains emerge as key challenges limiting domestic use of rainwater. Public education for house owners to invest in rainwater harvesting facilities and governmental support will be needed to increase investment in rainwater harvesting, purification and usage. © 2014 Taylor & Francis.
Keywords: Accra; Ghana; rainfall variability; rainwater harvesting; urban water